Efektivitas Pembelajaran IPA Terpadu Berbasis Model Immersed untuk Meningkatkan Respons Belajar Mahasiswa PGMI - Putra, Miftakhul Ilmi Suwignya; Anwar, M. Ansor; Solichin, Mujianto; Amrulloh, Amrulloh (Universitas Pesantren Tinggi Darul 'Ulum, 2018)
This study was aimed to describe the efectivity of science integrated learning with immersed model to increase student responses in PGMI. Students of 4th semester majoring in PGMI Unipdu Jombang, were subjected with the tested learning method. The study was conducted in February-June 2018 with experimental method. Students’ performance was assesed through cognitive tests, observation, and interviews. Results of this study indicate that science integrated learning with immersed model to improve students responses. Student responses to science integrated learning with immersed model is positive.